PERAN NOTARIS DALAM PERJANJIAN WARALABA ANTARA PT POS INDONESIA (PERSERO) PATI DENGAN BADAN USAHA PERSEORANGAN - Rifki Ardhianto; Lathifah Hanim (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
ABSTRACTThis study aims to determine the implementation and analyze the role of notary in a franchise agreement between PT Pos Indonesia (Persero) Pati with individual business entities, obstacles and solutions in the implementation of franchise agreement between PT Pos Indonesia (Persero) Pati with individual business entities and legal effects if the agreement A franchise between PT Pos Indonesia (Persero) Pati and individual business entities are not made by notarial deed.Method This research is empirical law research method, that is research based on implementation in effort to get primary data preceded by library research to get secondary data. The research was conducted at PT Pos Indonesia (Persero) Pati, and the overall data obtained was analyzed qualitatively.The results showed that the implementation and analysis of the role of notary in a franchise agreement between PT Pos Indonesia (Persero) Pati and individual business entities are agreements that are not contradictory to the law, religion, public order and morality. This means that the franchise agreement is valid and therefore the agreement becomes a law for those who make it, and binds both parties and the agreement is a standard reciprocal agreement because each party has equal rights and obligations put forward the principle of win-win solution Which are mutually beneficial. The obstacles that exist are the frenchisee can do wanprestasi which result in frenchisor loss. The solution is a franchisee before deciding to franchise must adjust to the franchise recipient character.Against the legal consequences that arise as a transaction that breeds the agreement, the franchise invariably involves two parties with independent interests and sometimes opposites. The principle of profit maximization is also essentially a source of differences in interests and disputes that can occur between the two parties. This great advantage can only be achieved by both parties if both parties can establish a mutually beneficial synergism.Keywords: Notary, Franchise Agreement, Individual Business Agency